Acceptor–acceptor conjugated copolymers based on perylenediimide and benzothiadiazole for all‐polymer solar cells. Issue 8 (6th February 2014) - Ge, Cong‐Wu; Mei, Chong‐Yu; Ling, Jun; Wang, Jin‐Tu; Zhao, Fu‐Gang; Liang, Long; Li, Hong‐Jiao; Xie, Yong‐Shu; Li, Wei‐Shi
ABSTRACT: Donor–acceptor (D–A) conjugated copolymers are one of known classes of organic optoelectronic materials and have been well developed. However, less attention has been paid on acceptor–acceptor (A–A) conjugated analogs. In this work, two types of A–A conjugated copolymers, namelyP1‐C n andP2‐C n ( n is the carbon number of their alkyl side chains), were designed and synthesized based on perylenediimide (PDI ) and 2, 1, 3‐benzothiadiazole (BT ). Different fromP1‐C n, P2‐C n polymers have additional acetylene π‐spacers betweenPDI andBT and thus hold a more planar backbone configuration. Property studies revealed thatP2‐C n polymers possess a much red‐extended UV–vis absorption spectrum, stronger π–π interchain interactions, and one‐order larger electron mobility in their neat film state thanP1‐C n . However, all‐polymer solar cells usingP1‐C n as acceptor component and poly(3‐hexyl thiophene) or poly(2, 7‐(9, 9‐didodecyl‐fluoene)‐ alt −5, 5′‐(4, 7‐dithienyl‐2‐yl‐2, 1, 3‐benzothiadiazole) as donor component exhibited much better performance than those based onP2‐C n . Apart from their backbone chemical structure, the side chains were found to have little influence on the photophysical, electrochemical, and photovoltaic properties for bothP1‐C n andP2‐C n polymers. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2014, 52, 1200–1215 Abstract : Two types of acceptor–acceptor conjugated copolymers are designed and synthesized based on perylenediimide (PDI) and benzothiadiazole (BT) with and without acetylene π‐spacers between PDI and BT units in their backbones. Their basic properties and photovoltaic performance as acceptor components for all‐polymer solar cells are investigated and compared.